2016
DOI: 10.1038/nphoton.2016.104
|View full text |Cite
|
Sign up to set email alerts
|

Phase-locked laser arrays through global antenna mutual coupling

Abstract: Phase locking of an array of lasers is a highly effective method in beam shaping because it increases the output power and reduces the lasing threshold. Here, we show a conceptually novel phase-locking mechanism based on 'antenna mutual coupling' in which laser elements interact through far-field radiations with definite phase relations. This allows a longrange global coupling among the array elements to achieve a robust phase locking in two-dimensional laser arrays. The scheme is ideal for lasers with a deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…[57,126] Due to the subwavelength transverse ridge dimension, the waveguide modes of photonic wire laser extend substantially outside of the active region core. [137] Nevertheless, the emission power is constrained by the small cavity size even though a large number of cavities are coupled. It was found that the power efficiency could be further improved (WPE ≈ 0.57% and PSE ≈ 450 mW A −1 ) when antenna loop structures were laterally integrated to the third-order DFB wire lasers to enlarge the effective emitting facet area.…”
Section: Power Efficiencymentioning
confidence: 99%
“…[57,126] Due to the subwavelength transverse ridge dimension, the waveguide modes of photonic wire laser extend substantially outside of the active region core. [137] Nevertheless, the emission power is constrained by the small cavity size even though a large number of cavities are coupled. It was found that the power efficiency could be further improved (WPE ≈ 0.57% and PSE ≈ 450 mW A −1 ) when antenna loop structures were laterally integrated to the third-order DFB wire lasers to enlarge the effective emitting facet area.…”
Section: Power Efficiencymentioning
confidence: 99%
“…Recently, emission beam with the very low divergence angle (<10 Â 10 ) has been demonstrated in a phased array of THz-QCLs and a THz-QCL vertical-external-cavity surfaceemitting-laser. 13,16 In the THz-MOPA-QCL, the beam divergence is determined by the dimensions of the emission aperture. Therefore, a tapered PA section with a widened diffraction grating will efficiently decrease the divergence angle.…”
Section: à3mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] Related results include third-order distributed feedback (DFB) lasers, 5,6 second-order DFB THzQCLs with dual slits, 7 THz-QCLs with a graded photonic heterostructure resonator, [9][10][11] phase-locked arrays of secondorder DFB lasers, [12][13][14] etc. However, to ensure that lasing occurs on transverse and longitudinal single-mode, the dimensions of the photonic coupling structure must be limited, thus restricting the available output power and increasing the divergence of the emitted beam.…”
mentioning
confidence: 99%
“…In acoustics, cylindrical ducts are of special interest for pressure wave propagation and turbocharger applications [33][34][35][36]. In photonics, axially symmetric media can be found in single-and multicore optical fibers, optical couplers, laser arrays, modulators, and Bragg gratings [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%